2021
DOI: 10.3389/fmed.2021.603558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Venous Thromboembolism in Critically Ill Patients With Coronavirus Disease 2019: A Meta-Analysis

Abstract: Background: Accumulating evidence suggests that coronavirus disease 2019 (COVID-19) is associated with hypercoagulative status, particularly for critically ill patients in the intensive care unit. However, the prevalence of venous thromboembolism (VTE) in these patients under routine prophylactic anticoagulation remains unknown. A meta-analysis was performed to evaluate the prevalence of VTE in these patients by pooling the results of these observational studies.Methods: Observational studies that reported the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 50 publications
0
29
1
2
Order By: Relevance
“…Given the evidence of direct invasion of the endothelium by SARS-CoV-2 ( 85 ) as well as the associated hypercoagulable state and increased risk of deep vein thrombosis and pulmonary embolism in acute infection ( 86 ), there is concern that venous thromboembolism (VTE) may play a role in a subset of patients with PASC. The prevalence of VTE in hospitalized acute COVID-19 patients may be as high as 25% ( 87 , 88 ) and one study found the rate of pulmonary embolism to be 24% for patients on the general wards and 49% for patients in the ICU ( 89 ). A meta-analysis of 3342 patients showed that pulmonary embolism and deep venous thrombosis occurred in 16.5% and 14.8%, primarily in the acute phase of infection, and more commonly in those admitted to the intensive care unit ( 90 ).…”
Section: Post-acute Sequelae Of Covid-19mentioning
confidence: 99%
“…Given the evidence of direct invasion of the endothelium by SARS-CoV-2 ( 85 ) as well as the associated hypercoagulable state and increased risk of deep vein thrombosis and pulmonary embolism in acute infection ( 86 ), there is concern that venous thromboembolism (VTE) may play a role in a subset of patients with PASC. The prevalence of VTE in hospitalized acute COVID-19 patients may be as high as 25% ( 87 , 88 ) and one study found the rate of pulmonary embolism to be 24% for patients on the general wards and 49% for patients in the ICU ( 89 ). A meta-analysis of 3342 patients showed that pulmonary embolism and deep venous thrombosis occurred in 16.5% and 14.8%, primarily in the acute phase of infection, and more commonly in those admitted to the intensive care unit ( 90 ).…”
Section: Post-acute Sequelae Of Covid-19mentioning
confidence: 99%
“…This results in a high incidence of venous and arterial thrombosis. Since the beginning of the pandemic, clinicians have reported that the incidence of venous thromboembolism in hospitalized patients with COVID-19 is high, particularly in ICU patients, and even among those who are receiving anticoagulation [87] , [88] , [89] , [90] , [91] . Although this incidence appears to have decreased later in the pandemic in the context of improved treatment, it remains high.…”
Section: Clinical Questionsmentioning
confidence: 99%
“…However, studies have shown that it can be associated with hypercoagulability leading to thromboembolism. Although venous thromboembolism is a common complication associated with COVID-19, arterial thrombosis and intracardiac thrombosis are not frequently described [2][3][4]. Herein, we report a case of a patient presenting to the emergency department with shortness of breath after recovering from COVID-19 a month ago and was found to have intracardiac thrombus.…”
Section: Introductionmentioning
confidence: 94%